Midwives' Experiences of Providing the “Inspirational Lecture” as a Care Intervention for Expectant Parents—A Qualitative Study - Bäckström, Caroline; Söderlund, Tina; Thorstensson, Stina; Mårtensson, Lena B.; Golsäter, Marie (Frontiers in Public Health, 2020)
Background: In most Western countries, ordinary parental classes exist and have become a well-established form of professional support within midwifery care, even though some of these classes lack evidence of benefits for the parents. A Swedish randomized controlled trial including an intervention as a pilot study, revealed that a type of parental preparatory professional support provided for expectant parents, the “inspirational lecture,” showed a tendency to be beneficial for parents' birth experience, and their perceived quality of parental couple relationship. However, there is no previous research on the midwives' experiences from providing the inspirational lecture. Carrying out research on midwives' experiences from providing the lecture, could bring future opportunities to provide a work-integrated learning (WIL) related to professionals' skills, and the pedagogic used. Aim: To elucidate midwives' experiences about providing the inspirational lecture as a care intervention for expectant parents. Methods: Midwives were interviewed and data were analyzed using qualitative content analysis. Results: The midwives strived to put childbirth into a comprehensive and manageable context for the expectant parents, during the inspirational lecture. For this, different approaches were used to make expectant parents understand how the parents themselves can be engaged participants in their own birth. Conclusion and Clinical Implications: The midwives used the inspirational lecture to provide the expectant parents with knowledge about how they, as a parental couple, could cooperate and feel safe in relation to the upcoming birth. This could be understood as if the midwives were striving to facilitate the integrative power of the parental couple, which is the couples' ability to gather their joint power. These results can assist midwives and serve as a reference for providing parental classes for expectant parents with a focus on promoting both the parents' individual as well as mutual skills.